A NONLINEAR CONVERSION MODEL FORM ITRFYY TO CGCS2000 - F. Wang; P. Zhang; Z. Y. Sun; Q. L. Zhang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
At present, ITRS series reference frameworks are widely used in the world. The results of GNSS are mostly based on the ITRF framework. Transform from ITRF to CGCS2000 is not easy, which restricts the promotion and use of CGCS2000. The conversion relationship between CGCS2000 and ITRF framework has imminent practical significance. This paper constructs the epoch reduction and frame conversion two-steps model which estimated the nonlinear model to solve the appeal problem. Effective test show that the nonlinear model accesses an improvement in not only precession but also accuracy relative to the tradition model.